Microplastic Production from Plastic Recycling Village in Van Lam, Hung Yen Province - Minh Hen, Pham; Manh Hoang, Nguyen; Huu Thinh, Dao; Hai Long, Le; Duc Canh, Nguyen; Huu Cong, Vo (VNU Journal of Science: Earth and Environmental Sciences, 2022)
This study aims to evaluate the microplastic production and its occurence in water and sediment from Minh Khai commune, Hung Yen province. Research on the scales and methods of plastic recycling was conducted in 10 different manufacturing facilities. We quantified and classified microplastics present in water, sediment, and aquatic animal samples in the canals that receive      wastewater from the production facilities. The results show that the plastic recycling village currently has 48 plastic recycling facilities in operation, the average amount of recycled plastic is 2.21 ± 0.095 tons/household/day. There are 8 main disposal points that discharge wastewater                    . The measured discharging rate is 15.1-16.8 m 3 /h. The microplastic content in the environment was found to be 0.33 ± 0.05 g/L, in which microplastics had 0.03 g/L. In river water, of all the microplastic we found, 67% were plastic flakes and 33% were other plastics. In the sediment, 0.45% were microplastics and 4.63% were plastic fragments. This is the first study to detect and quantify microplastics in the environment from the plastic recycling village. It is necessary to expand research in wastewater discharging points to complete the process of quantifying and classifying microplastics.